الإحالة في ترجمة "جون غروجون" (jean Grosjean) لمعاني سورة الأنعام The reference in Jean Grosjean’s translation of the meanings of Surah “Al-Anam” (مجلة إحالات, 2025)
ملخص: إن نص الترجمة المثالي هو النص الذي يكون اتساقه تابعا لاتساق النص في اللغة المصدر مع احترام متطلبات اللغة الهدف، أي أنه ينبغي على المترجم أن يفهم نظام التماسك أو الاتساق في اللغة الأصل ثم يحاول نقله أو تكييفه مع اللغة الهدف، ومن بين أهم الوسائل التي تحقق الاتساق نجد الإحالة التي تعبر عن تلك العلاقة بين ألفاظ النص وعناصر أخرى قد تكون داخل هذا النص أو خارجه بشرط اتصال الدلالة فيما بينها. في هذا الإطار سيكون موضوع هذا البحث الذي يهدف إلى ربط الإحالة بالترجمة عن طريق دراسة كيفية انتقالها من النص المصدر إلى النص الهدف وذلك في ميدان ترجمة معاني القرآن الكريم، عن طريق دراسة بعض النماذج من ترجمة "جون غروجون" لمعاني سورة الأنعام، للإجابة على الإشكالية المتمثلة في كيفية تعامل هذا المترجم مع عنصر الإحالة في ترجمته لمعاني هذه السورة الكريمة.Abstract: The ideal translation text follows the cohesion of the source text with respect to the target language’s requirements, that’ s to say the translator must understand the system of cohesion in the (SL) and then try to adapt or transfer it to the (TL). Among the most important means that achieve the cohesion is the reference which expresses the relationship between the words of the text and other elements that may be inside or outside this text provided that the significance is connected to each other. In this context, This research aims to link the reference with translation through the study of its transfer from the source text to the target text in the field of translating the meanings of the Holy Koran by the study of some models from the translation of “Jean Grosjean” of the meanings of Surah Al-Anam to solve the research problem of how this translator deals with the element of reference in his translation of the meanings of this noble Surah.